Cloud Security Challenges: An In-Depth Examination of Risks and Mitigation Strategies - Srikanth Bellamkonda (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The rapid adoption of cloud computing has revolutionized the way organizations manage and store data, offering unparalleled scalability, flexibility, and cost-efficiency. However, this shift also introduces a myriad of security challenges that can undermine the benefits of cloud services. This paper explores the primary security challenges associated with cloud computing, including data security and privacy, compliance and legal issues, access control, insider threats, and vulnerabilities in multi-tenancy environments. Through a comprehensive literature review and analysis of real-world case studies, the study highlights the complexities of securing cloud infrastructures and the limitations of existing security measures. Additionally, the research examines emerging technologies and best practices aimed at mitigating these challenges. The findings underscore the necessity for a multi-layered security approach and proactive strategies to enhance cloud security, ensuring the protection of sensitive data and the resilience of cloud-based systems. Recommendations are provided for organizations to strengthen their cloud security posture, emphasizing the importance of continuous monitoring, robust encryption, and comprehensive governance frameworks. The paper concludes by identifying future research directions to address evolving cloud security threats and optimize security solutions in dynamic cloud environments.